Plasmid-Mediated Quinolone Resistance; Interactions between Human, Animal, and Environmental Ecologies - POIREL, Laurent; Cattoir, Vincent; Nordmann, Patrice (Frontiers in Microbiology, 2012)
Resistance to quinolones and fluoroquinolones is being increasingly reported among human but also veterinary isolates during the last two to three decades, very likely as a consequence of the large clinical usage of those antibiotics. Even if the principle mechanisms of resistance to quinolones are chromosome-encoded, due to modifications of molecular targets (DNA gyrase and topoisomerase IV), decreased outer-membrane permeability (porin defect) and overexpression of naturally-occurring efflux, the emergence of plasmid-mediated quinolone resistance (PMQR) has been reported since 1998. Although these PMQR determinants confer low-level resistance to quinolones and/or fluoroquinolones, they are a favorable background for selection of additional chromosome-encoded quinolone resistance mechanisms. Different transferable mechanisms have been identified, corresponding to the production of Qnr proteins, of the aminoglycoside acetyltransferase AAC(6’)-Ib-cr, or of the QepA-type or OqxAB-type efflux pumps. Qnr proteins protect target enzymes (DNA gyrase and type IV topoisomerase) from quinolone inhibition (mostly nalidixic acid). The AAC(6’)-Ib-cr determinant acetylates several fluoroquinolones, such as norfloxacin and ciprofloxacin. Finally, the QepA and OqxAB efflux pumps extrude fluoroquinolones from the bacterial cell. A series of studies have identified the environment to be a reservoir of PMQR genes, with farm animals and aquatic habitats being significantly involved. In addition, the origin of the qnr genes has been identified, corresponding to the waterborne species Shewanella sp. Altogether, the recent observations suggest that the aquatic environment might constitute the original source of PMQR genes, that would secondly spread among animal or human isolates.